Self-regulated learning in English-language learners who are persisting despite failure on a high school exit exam. Issue 2 (10th June 2019) - Krishnan, Kalyani; Li, Chieh; Kruger, Louis; Kimble, Edward; Aki, Gina; Ruah, Rachel
Abstract : Purpose: This study aims to explore whether English-language learners (ELLs) who have struggled to pass a high school exit exam (HSEE) self-report that they are able to self-regulate their learning. It is of interest to find out whether, in addition to limited English proficiency, these students are struggling to exert control over their learning. Design/methodology/approach: Using semi-structured interviews, the study sought the perspectives of eight ELLs who had repeatedly failed their state-mandated HSEE. Interviews were transcribed using a modified grounded theory approach, and thought units were coded with a focus on the following elements of SRL: self-understanding, goal directedness, flexibility and strategy use. Findings: Results indicated that all interviewees demonstrated a greater, more specific awareness of their academic weaknesses than their strengths. Half the interviewees demonstrated an awareness of how they learned. Similarly, half of them verbalized that they approached learning flexibly. None of the interviewees reported using evidence-based strategies. However, all interviewees were goal-oriented. Research limitations/implications: This research approach may limit the external validity of the results. The richness of the data may also be limited because interviews were conducted in English. Practical implications: The findings from this study have implications for educating ELLs in an era of standards-based education and helping them pass HSEEs. Social implications: These results also have implications for advancing social justice through informed educational policy. Originality/value: This paper fills a gap in the literature by extending the theory of SRL, which is associated with academic success in diverse students, to ELLs, a rapidly growing demographic in US public schools that is struggling to achieve academic success.